Plan de negocios para la creación de una empresa productora y comercializadora de arándano en la provincia de Pichincha - Fierro Almeida, Kevyn Santiago (2018)
The purpose of this business plan is to create a company for the production and merchandising of the blueberry fruit based in the province of Pichincha. This is due to the recent growth in the trend of fruit consumption. The blueberry is a fruit family of the "berries" that in the country has begun to have an important reception, although it is a fruit that in countries like Chile and Peru already has an important acceptance, nowadays in our country this fruit is not produced in large quantities, since it is not well known. Once the external factors have been analyzed, there is a positive outlook for the implementation of the project due to the facilities given to the agricultural industry and loans granted by BanEcuador at a low interest rate. Also, in the analysis of the industry you can see the feasibility for the implementation of the project since there are not many competitors due to the current entry barriers. Through the market research carried out, it was determined that people do not know about the benefits of a fruit such as the blueberry, as well as companies that produce it. It was found that the people surveyed mostly consume fruits every day and buys them between two to three times a week with an average spending between five to ten dollars, for this reason we have giving the price of two dollars with twenty-five cents for every 125 grams.